Predicting Hardwood Porosity Domains: Toward Cascading Computer-Vision Wood Identification Models - Owens, Frank C.; Ravindran, Prabu; Costa, Adriana; Shmulsky, Rubin; Wiedenhoeft, Alex C. [UNESP] (BioResources, 2024)
Prior work on computer-vision wood identification (CVWID) for North American hardwoods yielded two independent deep learning models – a 22-class model for diffuse-porous woods and a 17-class model for ring-porous woods – but did not address semi-ring-porous woods nor provide a CVWID solution for an unknown specimen without a human first determining which model to deploy. As untrained human operators would lack the anatomical proficiency to differentiate among porosity domains, it is necessary to develop a consolidated model that can identify diffuse-, ring-, and semi-ring-porous woods. Previous research suggests that prediction accuracy might decrease as class number grows. A potential strategy to reduce the number of classes a CVWID system must consider at a time is to hierarchically deploy a cascade of models. In pursuit of a unified model that can cover North American hardwoods of all porosity types, this study compared the accuracies of a consolidated 39-class (ring-+ diffuse-porous) model and a consolidated 42-class (ring-+ diffuse-+ semi-ring-porous) model with a two-tiered, cascading model scheme whereby images are first differentiated into three porosity domain classes and then again into only those taxonomic classes with that porosity. The results showed that the cascading model scheme can mitigate the accuracy reductions incurred by the 42-class model and nearly eliminate the occurrence of cross-domain misidentifications.
Keywords: Cascading models; Computer vision; Deep learning; Machine learning; Porosity domain; Wood identification; XyloTron